A needs analysis of the speaking skills of enforcement officers at a local public agency / Siti Ruhana Suref - Siti Ruhana , Suref (2017)
Working in an environment of handling English speakers from local community or multi-nationality seems to be a very pressing situation for employees who were not proficient in their communication skills particularly in English speaking skills. In today’s globalized work contexts, it has become an essential requirement to be able to communicate effectively when performing daily job activities. This study investigates the needs in English speaking skill of the enforcement officers of a large Local Public Agency (LPA). This study also explores the problems of English speaking skills faced by the officers with English speaking clients. In addition, this study also analyses the type of communication strategies used by the officers to cope with their English speaking problems. In responding to the research objectives, a questionnaire was distributed to 100 officers working in four different sections of the enforcement unit. All the officers were the front liners of the LPA and have direct handling with English speakers either from the local communities or foreigners. Interviews were conducted in two sessions; the first session was held randomly with officers from different units in the LPA and the second session with a different set of pre-selected ten officers using structured open-ended questions. In addition, fieldwork observations were also performed to provide additional data to the research. Findings revealed that the officers were in need of English language training courses to strengthen their proficiency and to overcome their problems in English speaking skills. It was also discovered that the officers use various kinds of strategies to understand and to respond confidently whilst avoiding unnecessary misunderstanding or miscommunication during oral activities. The result of this study would benefit the management, stakeholders and the officers in terms of recognizing the importance of good speaking skills and for the agency’s training planner to design tailor-made courses that are specific to the needs of the enforcement officers in particular.